Criminal Law Politics and Reform to Strengthen Law Enforcement Roles in Indonesia in Combatting Narcotics Crimes - Pambudi, Pambudi; Redi, Ahmad (Asian Journal of Social and Humanities, 2024)
This research aims to analyze the criminal law policy on narcotics in Indonesia and evaluate the reform of strengthening the role of law enforcement officials in combating narcotics offenses. The study focuses on examining the existing legal framework governing narcotics crimes, assessing the effectiveness of its implementation, and identifying the challenges faced in the law enforcement process. Through a comprehensive analysis, this research highlights various obstacles, including limitations in resources, inconsistencies in legal interpretation, and gaps in inter-agency coordination, which hinder the effectiveness of narcotics law enforcement. Furthermore, this study explores reform efforts to enhance the professionalism, capacity, and integrity of law enforcement officials as key agents in addressing narcotics-related offenses. It emphasizes the importance of improving training, adopting technology-driven approaches, and fostering accountability to ensure a more transparent and efficient enforcement system. The findings of this research are expected to contribute to the development of a more effective, just, and sustainable law enforcement policy that can better respond to the ongoing threat of narcotics in Indonesia. By addressing systemic challenges and implementing strategic reforms, this study advocates for a holistic approach to combating narcotics offenses and safeguarding society from their adverse impacts.